Mixing Performance of a Novel Flat-Bottom Vertical Feed Mixer - Jo, Hyunwoong; Kong, Changsu; Nam, Doo Seok; Kim , Beob Gyun (International Journal of Poultry Science, 2015)
The objective of the present study was to test mixing performance of a flat-bottom vertical mixer. The mixer has a capacity of 250 liter with 430 mm height and 900 mm diameter. A diet was formulated to contain 69.5% corn, 27.5% soybean meal, 0.9% limestone, 0.8% dicalcium phosphate, 0.5% vitamin-mineral premix, 0.45% salt and 0.4% chromic oxide. The mixing performance of the mixer was tested with 80 kg batch in triplicate for 30, 180, 300 and 420 sec. At the end of each mixing, 100 g of samples were collected from the initial 5, 30, 60 and 95% of feed discharged from the spout end of the mixer. The 4 samples from each mixing time were analyzed for the concentrations of crude protein. The coefficients of variation of crude protein among the samples from each mixing of 30, 180, 300 and 420 sec were 14.8, 7.4, 6.7 and 6.0%, respectively. A broken-line analysis was conducted to estimate the minimum mixing time. The result indicated that the most suitable mixing time was 202 sec (R2 = 0.99; p = 0.077). In conclusion, at least 200 sec of mixing is required for optimum mixing performance of the novel feed mixer.